Neoadjuvant toripalimab combined with chemotherapy in locally advanced HNSCC - Wang, Zhaoyang; Yang, Sheng; Yan, Dangui; Zhang, Ye; Zhang, Xiwei; Zhang, Fa; Zhao, Xiaohui; Zhang, Zongmin; Liu, Shaoyan; Gui, Lin; An, Changming (Frontiers in Oncology, 2025)
IntroductionTo determine the safety and efficacy of neoadjuvant toripalimab combined with chemotherapy in locally advanced head and neck squamous cell carcinoma (LA-HNSCC).Patients and methodsThis single-arm investigator-initiated trial was conducted at a tertiary cancer hospital in China. The untreated LA-HNSCC patients received two cycles of neoadjuvant paclitaxel and cisplatin (TP) + toripalimab regimen (paclitaxel 175 mg/m2 d1, cisplatin 75 mg/m2 d1, and toripalimab 240 mg d1, every 3 weeks). Surgery or chemoradiotherapy (CRT) was determined via the patient–doctor consensus. The primary endpoints were objective response rate (ORR) and safety.ResultsThe study enrolled a total of 23 patients. All the patients completed the entire treatment course with an ORR of 78.3% (18/23). Any grades of treatment-related adverse events (TRAEs) were reported in 12 patients (52.2%), and three patients experienced grade 3–4– TRAEs. No delay for curative treatment was observed. Twelve patients underwent radical surgery, and six patients developed pathological complete response (pCR), with a pCR rate of 50%. With a median follow-up of 15 months, 12 surgery patients maintained event-free survival; however, three out of 11 who received CRT suffered from local recurrence or metastases.ConclusionsNeoadjuvant TP + toripalimab for LA-HNSCC showed high ORR and pCR rates with a good safety profile.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=231832, identifier ChiCTR2400091148.